A position paper on the management of itch and pain in atopic dermatitis from the International Society of Atopic Dermatitis (ISAD)/Oriented Patient‐Education Network in Dermatology (OPENED) task force. (8th October 2020) - Misery, L.; Belloni Fortina, A.; El Hachem, M.; Chernyshov, P.; von Kobyletzki, L.; Heratizadeh, A.; Marcoux, D.; Aoki, V.; Zaniboni, M.C.; Stalder, J.‐F.; Eichenfield, L.F.
Abstract: Atopic dermatitis (AD) is a disease that can have a high impact on quality of life, especially due to itch and skin pain. This paper utilizes expertise from members of the International Society of Atopic Dermatitis (ISAD)/Oriented Patient‐Education Network in Dermatology (OPENED) task force to review the epidemiology, pathophysiology and exacerbating factors of itch and pain in atopic dermatitis. General principles of treatment are provided, as well as a more detailed evaluation of topical and systemic therapies. Educational and psychological approaches to itch and pain in atopic dermatitis are proposed, along with expert recommendations for the management of itch and pain in atopic dermatitis.